2011
DOI: 10.1155/2011/976196
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Brazilian Propolis against Herpes Simplex Virus Type 1 Infection in Mice and Their Modes of Antiherpetic Efficacies

Abstract: Ethanol extracts (AF-06, 07, and 08, 10 mg/kg) of Brazilian propolis were administered orally to cutaneously herpes simplex virus type 1 (HSV-1)-infected mice three times daily on days 0 to 6 after infection to evaluate their efficacies against HSV-1 infection and significantly limited development of herpetic skin lesions. AF-07 and 08 significantly reduced virus titers in brain and/or skin on day 4 without toxicity, but AF-08 had no anti-HSV-1 activity in vitro. AF-06 and 08 significantly enhanced delayed-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 28 publications
1
62
0
1
Order By: Relevance
“…The anti‐HSV effect of propolis was tested in an in‐vitro and in‐vivo study and propolis was found to have an inhibitory effect on viral infection probably owing to the prevention of virus absorption into the host cells and/or inhibition of an internal step(s) during the viral replication cycle, thus preventing the appearance and development of symptoms in vivo . In another study, Brazilian propolis showed not only direct anti‐HSV‐1 activity but also immunological activity against intradermal HSV‐1 infection in mice …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The anti‐HSV effect of propolis was tested in an in‐vitro and in‐vivo study and propolis was found to have an inhibitory effect on viral infection probably owing to the prevention of virus absorption into the host cells and/or inhibition of an internal step(s) during the viral replication cycle, thus preventing the appearance and development of symptoms in vivo . In another study, Brazilian propolis showed not only direct anti‐HSV‐1 activity but also immunological activity against intradermal HSV‐1 infection in mice …”
Section: Discussionmentioning
confidence: 96%
“…In another study, Brazilian propolis showed not only direct anti-HSV-1 activity but also immunological activity against intradermal HSV-1 infection in mice. 72 Repair of oral wounds Propolis in aqueous alcohol solution exerted a small analgesic and anti-inflammatory effect and also aided repair of intra-buccal surgical wounds after sulculoplasty by modified Kazanjian technique. 73 Topical application of propolis hydro-alcoholic solution was found to accelerate epithelial repair after tooth extraction but had no effect on socket wound healing.…”
Section: Antiviralmentioning
confidence: 99%
“…SHIMIZU, et al (2011), utilizando um modelo animal concluíram que a própolis não apresenta somente uma atividade direta contra o HSV-1, mas também uma atividade imunológica contra a infeção intradérmica causada por este vírus em ratos. Os resultados de Yildirim, et al (2016) utilizando própolis demonstraram que ela apresenta importantes efeitos antivirais comparados ao Aciclovir.…”
Section: Discussionunclassified
“…A number of studies conducted in several different laboratories also indicated that propolis, as well as some of its components, was active in increasing the secretion of several cytokines and the mechanisms involved are not clear yet. (9)(10)(11)(12)(13)(14) It should be pointed out that overproduction of some cytokines is not beneficial and frequently associated with inflammatory response or autoimmunity, as raised kindly by Dr. Salvatore Chirumbolo.…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%